2022
DOI: 10.21203/rs.3.rs-1365268/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meeting nature-positive goals for an organisation’s food system

Abstract: Organisations are increasingly committing to ‘nature-positive’ targets, in line with proposed international goals. However, there are few worked examples showing how to feasibly achieve these targets. Here, we set out a novel approach to achieving nature-positive targets with respect to the embodied biodiversity impacts of an organisation’s food consumption. We quantify these impacts using a comprehensive database of life-cycle environmental impacts from food and provide exploratory strategies to meet defined … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…2023). In particular, there is an interest in understanding how HEIs can contribute to this larger effort by reducing the amount of meat consumed within campus environments (Ruiz-Mallén Heras, 2020; Sherry and Tivona, 2022;Taylor et al, 2023). Despite the empirical progress that has been made over the last two decades, there has been little research to date reflecting on how useful these interventions have been in promoting voluntary changes in food choice within university settings.…”
Section: Discussionmentioning
confidence: 99%
“…2023). In particular, there is an interest in understanding how HEIs can contribute to this larger effort by reducing the amount of meat consumed within campus environments (Ruiz-Mallén Heras, 2020; Sherry and Tivona, 2022;Taylor et al, 2023). Despite the empirical progress that has been made over the last two decades, there has been little research to date reflecting on how useful these interventions have been in promoting voluntary changes in food choice within university settings.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable shift away from business as usual is needed for the private sector to align with the principles in Box 1 and make a substantive contribution to delivering GBF goals (Panwar 2023). For example, case studies quantifying the biodiversity footprint of the University of Oxford, and outlining Nature Positive strategies for the food system of an individual Oxford college, both identified that rapid, ambitious, large-scale institutional change would be necessary to achieve Nature Positive aligned goals (Bull et al 2022b;Taylor et al 2022). For businesses, this poses the challenge of reducing impacts and increasing efficiencies without compromising business-critical activities, while also taking actions to deliver additional conservation gains and remove barriers to a nature positive future (Booth et al 2023a partners is needed to answer these questions and help to drive technological, economic and policy innovations for a nature positive future.…”
Section: Introductionmentioning
confidence: 99%